STRATEGI PEMBELAJARAN BERORIENTASI AKTIVITAS SISWA - NURHASNAWATI NURHASNAWATI (An-Nida', 2011)
Every teacher in educating their student have the strategies vary. Strategy adopted will depend on the teacher approaches used, while how to run a strategy that can be assigned vatious learning methods. In an effort to execute a method, of learning techniques that teachers can determine it deems relevant to the method, and the use each other. The strategy used is closely associated with the learning process that can transform experience into knowledge, knowledge into understanding, comprehension be comes wisdom, and wisdom can create an activity student study independently